2000
DOI: 10.1590/s0100-204x2000000500008
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of maize and cowpea to intercropping

Abstract: The effect of intercropping on plant water status, gas exchange and productivity of maize (Zea mays L.) cv. Centralmex, and cowpea (Vigna unguiculata L. (Walp)) cv. Pitiuba were evaluated under semi-arid conditions at the Embrapa-Centro de Pesquisa Agropecuária do Trópico Semi-Árido (CPATSA) at Petrolina, PE, Brazil. The treatments were: maize and cowpea as sole crops, at a population of 40,000 plants ha-1, and intercropped at a population of 20,000 plants ha-1. The results obtained in this paper appear to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…In a similar study, [31] also did not find any significant differences in LAI between maize monocrop and maize intercropped with sugar beans or groundnuts. These findings are consistent with results of [36] who did not find any significant differences in LAI between sole maize and maize intercropped with cowpea. The leaf area (LA) describes the size of the assimilatory apparatus of a plant stand and is the main factor that determines the rate of dry matter production in a closed stand.…”
Section: Plant Population Of Maize At 9 Wap and At Harvestsupporting
confidence: 92%
“…In a similar study, [31] also did not find any significant differences in LAI between maize monocrop and maize intercropped with sugar beans or groundnuts. These findings are consistent with results of [36] who did not find any significant differences in LAI between sole maize and maize intercropped with cowpea. The leaf area (LA) describes the size of the assimilatory apparatus of a plant stand and is the main factor that determines the rate of dry matter production in a closed stand.…”
Section: Plant Population Of Maize At 9 Wap and At Harvestsupporting
confidence: 92%
“…Another factor that could have contributed to the high maize grain yield is that of reduced evapotranspiration of the component crops resulting in better water use efficiency. This agrees with [10] who found out that the modification of the light environment by the plant canopy affected positively the water relations of the intercropped plants by increasing the water use efficiency which would result in increased yields particularly benefiting farmers who live in the arid and semi-arid areas like those found in natural region III-IV in Zimbabwe. Modification of the light environment also means that the soil temperatures are kept to at a minimum hence less moisture is lost to the atmosphere through soil surface evaporation hence maintaining the soil moisture regime thus increasing water use efficiency by the component crops.…”
Section: Effect Of Intercropping On Grain Yieldsupporting
confidence: 90%
“…One of the main principles of CA encourages farmers to mix and rotate crops of different species [9]. The mixing of crops of different species ensures maximum exploration of the different layers of the soil profile at different times which will result in less competition between the component crops and attainment of better yield [10]. [11] advocated that intercropping increased crop productivity and yield in dry areas.…”
Section: Introductionmentioning
confidence: 99%
“…7), indicating no detrimental competition between maize and cowpea. Cowpea creates a "live mulch" that lowers surface soil temperature and evaporation, thus improving water conservation compared with sole cropping (Lima Filho, 2000). Rusinamhodzi et al (2012) also reported LER values ranging from 1 to 2.4 in additive and substitutive maize/cowpea intercropping in central Mozambique.…”
Section: Promising Tailored Optionsmentioning
confidence: 99%